If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(2t + 9) = -88 Reorder the terms: -8(9 + 2t) = -88 (9 * -8 + 2t * -8) = -88 (-72 + -16t) = -88 Solving -72 + -16t = -88 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + -16t = -88 + 72 Combine like terms: -72 + 72 = 0 0 + -16t = -88 + 72 -16t = -88 + 72 Combine like terms: -88 + 72 = -16 -16t = -16 Divide each side by '-16'. t = 1 Simplifying t = 1
| n-15=32 | | -17+19+19-(19-(-17))= | | 4-5k=-8-5k | | 8*a-3(2*a+5)=13 | | 6-y=3y+8 | | 4(f-3)=-16 | | 4=20n | | (c-25)(c+50)=0 | | 3x+5m-2x= | | 4y=-64 | | 21x+12=25-2x | | -10(s+1)=72 | | 4*y-(y-4)=-20 | | 11=0.5(3+7x) | | 40=10+z | | 14x+1+5x-7=89 | | 8a-19=3a+5 | | z+5-4*z=8 | | 70-t=50 | | 9x+10=17+2x | | 81m^2=49 | | 7+3(2x+5)+4=2x-2(3x+8) | | 2(-x+1)-6x=30 | | c-2*c-5-5*c=7 | | 8e^2+64e=-56 | | -2t+4t+-7s=9s | | 3+x=7x-21 | | p+15=15 | | 5(-3x+5)=25 | | 16=10c-c^2 | | 3*w+4*w-2=12 | | 5m+8=78 |